2007
DOI: 10.1016/j.heares.2006.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dependence of cochlear cells and structures injured by noise

Abstract: The acute and permanent effects of a single damaging noise exposure were compared in CBA/J, C57BL/6 (B6), and closely related strains of mice. Two hrs of broadband noise (4-45 kHz) at 110 dB SPL led to temporary reduction in the endocochlear potential (EP) of CBA/J and CBA/CaJ (CBA) mice and acute cellular changes in cochlear stria vascularis and spiral ligament. For the same exposure, B6 mice showed no EP reduction and little of the pathology seen in CBA. Eight weeks after exposure, all mice showed a normal E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
63
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(84 citation statements)
references
References 79 publications
(109 reference statements)
18
63
2
Order By: Relevance
“…6), in good agreement with previous studies in this and other mouse strains (Sadanaga and Morimitsu, 1995;Wu and Marcus, 2003;Ohlemiller and Gagnon, 2007b). There was no decline with age and EP remained high even in animals with severe elevations in ABR threshold.…”
Section: The Endocochlear Potential (Ep) Is Stable With Agingsupporting
confidence: 91%
“…6), in good agreement with previous studies in this and other mouse strains (Sadanaga and Morimitsu, 1995;Wu and Marcus, 2003;Ohlemiller and Gagnon, 2007b). There was no decline with age and EP remained high even in animals with severe elevations in ABR threshold.…”
Section: The Endocochlear Potential (Ep) Is Stable With Agingsupporting
confidence: 91%
“…The small increase in auditory thresholds as indicated by the ABR in the CBA/CaJ mice with age is in keeping with other studies, and this strain has been shown to maintain hearing well into advanced age [29]. There was a significant, albeit small, drop in the magnitude of EP in older mice, which has also been reported by Ohlemiller and Gagnon [30]. As EP provides a component of the driving force for hair cell transduction, EP magnitude and auditory threshold, as measured by sensitivity of individual spiral ganglion neurons, are intimately correlated [31].…”
Section: Discussionsupporting
confidence: 90%
“…S1) and demonstrated slightly smaller reductions in SEP magnitudes in response to trauma than did 40AG13, suggesting that genetic background differences affect hearing sensitivity and response to physiological perturbation. Genomic differences have significant effects on the susceptibility and response to interventions in NIHL and age-related hearing loss in mice (32,33) and humans (34). A strength of Drosophila is that rapid generation times, large number of lines, and diverse molecular and genomic tools enable large-scale and fine-resolution genetic studies, making it an excellent system to study interactions between genetic background effects and NIHL.…”
Section: Discussionmentioning
confidence: 99%